Differentiation of Microvessel Density Based on The Breast Cancer Patient Characteristics Including Age, Stage, Tumor Size, and Lymph Node Metastasis - Salsabila, Tasya; Pratiwi, Sari Eka; Trianto, Heru Fajar; Ilmiawan, Muhammad In'am; Lestari, Desriani; Fitrianingrum, Iit; Hartono, Henky (http://dharmais.co.id/, 2024)
Background: Breast cancer is the most common malignant tumor in the world and Indonesia. One well-known prognostic marker is microvessel density (MVD), the numerical value of angiogenesis. In recent years, it has been recognized that tumor growth depends on angiogenesis. Therefore, this study aimed to determine the differentiation of MVD based on the breast cancer patients' characteristics including age, stage, tumor size, and lymph node metastasis in the Anatomical Pathology Laboratory of Soedarso Hospital. Methods: This research was an observational study with a cross-sectional approach. The study was conducted by observing the slides of Hematoxylin-Eosin (HE) in breast cancer patients. Samples were taken using the total sampling technique. The samples were observed by two observers. 51 tissue preparations met the inclusions and exclusions criteria. MVD cut-off points are taken by calculating the median. Research analysis was using the Kruskal-Wallis test in SPSS version 24. Results: All samples of this study were women and had invasive ductal carcinoma. Breast cancer tends to occur in patients aged 48-53 years, has stage III, lymph node metastasis (N2). The patients have a low MVD rate but have a large tumor size (T4). Kruskal Wallis test showed that there was a differentiation of MVD based on age (p = 0.029). While, there was no differentiation of MVD based on stage (p=0.974), tumor size (0.069), and lymph node metastasis (0.571). Conclusions: There was a differentiation of MVD based on the age of breast cancer patients in the Anatomical Pathology Laboratory at Soedarso Hospital.